The Impact of Artificial Intelligence Applications on Digital Banking in Turkish Banking Industry - Serkan Demirel; Murat Topcu (Advances in Human-Computer Interaction)
This paper presents the effects of chat box (C.B.) and video call (V.C.) artificial intelligence applications, which are becoming increasingly common in the banking system in parallel with the development of information systems on the number of digital banking users, and the relationship between the variables is investigated. The data set of the variables consists of a total of 44 observation points between the 1st quarter of 2012 and the 4th quarter of 2022. The cointegration relationship between the variables is examined using the ARDL cointegration test. According to the F statistic results for cointegration hypothesis testing, there is a statistically significant relationship between the variables at a 1% significance level. In the long run, a 1% increase in Chat Box users causes an increase of approximately 0.2% in the number of mobile banking users. A 1% increase in Chat Box users in the short term increases the number of mobile banking users in the current period by approximately 0.03%. A 1% increase in video call users in the long term causes an increase of approximately 0.04% in the number of mobile banking users. A 1% increase in the number of video calls in the current period increases current period mobile banking applications by approximately 0.005%. It has been determined that the effect of chat box applications on mobile banking is higher than that of video call applications. In addition, there is a close correlation between mobile banking and the independent variable chat box, no correlation between mobile banking and video calling, and a moderate correlation between chat box and video calling. All findings mean that artificial intelligence applications positively contribute to the expansion of mobile banking.